Prevalence and abundance of Cryptosporidium parvum and Giardia spp. in wild rural rodents from the Mazury Lake District region of Poland - Bajer, Anna; Bednarska, M.; Pawelczyk, A.; Behnke, Jerzy M.; Gilbert, Francis S.; Sinski, Edward (Cambridge University Press, 2002)
Prevalence and abundance of Cryptosporodium parvum and Giardia spp. were studied in 3 species of rodents from forests and abandoned agricultural fields in N.E. Poland (Clethrionomys glareolus n=459; Microtus arvalis n=274; Apodemus flavicollis n=209). Overall prevalence was consistently higher in the voles compared with A. flavicollis (70±6, 73±0 and 27±8% respectively for C. parvum and 93±9, 96±3 and 48±3% respectively for Giardia spp.). Prevalence and abundance of infection also varied markedly across 3 years with 1998 being a year of higher prevalence and abundance with both species. Fewer older animals (especially C. glareolus and M. arvalis) carried infection with C. parvum and infections in these animals were relatively milder. Although seasonal differences were significant, no consistent pattern of changes was apparent. Host sex did not influence prevalence or abundance of infection with C. parvum, but made a small contribution to a 4-way interaction (in 5-way ANOVA) with other factors in the case of Giardia spp. The 2 species co-occurred significantly and in animals carrying both parasites there was a highly signficant positive correlation between abundance of infection with each, even with between-year, seasonal, host age, sex and species differences taken into account. Quantitative associations were confined to the 2 vole species in the study. These results are discussed in relation to the importance of wild rodents as reservoir hosts and sources of infection for local human communities.